Miniaturized dual-stub resonator of bandstop filter / Farawahida Ahmad Ramli - Ahmad Ramli, Farawahida (2011)
in this paper a capacitor is proposed to tune the resonant frequency of dual-stub resonator of bandstop filter to miniaturize the circuit size. The capacitors is attach to an open circuit dual-stub to tune the 2 GHz dual-stub resonant to lower frequency which is I GHz. The complete simulated resonator with capacitors and the frequency response using the fabricated circuit on FR-4 substrate is present in this paper. The dual-stub resonator has achieved 50.2% circuit miniaturized and suitable for processor and wireless network system applications.